Pathogenetic relevance of HLA class II expressing thyroid follicular cells in nontoxic Goiter and in Graves' disease. - Grubeck-Loebenstein, B; Londei, M; Greenall, C; Pirich, K; Kassal, H; Waldhäusl, W; Feldmann, M (1988)
HLA class II expressing thyroid follicular cells are found not only in classical thyroid autoimmune diseases, such as Graves' disease, but also in presumably nonautoimmune thyroid disorders such as nontoxic goiter. In this study the immunostimulatory function of the HLA class II expressing thyroid follicular cells derived from patients with nontoxic goiter and with Graves' disease was compared by assessing their capacity to stimulate allogeneic and autologous peripheral blood mononuclear cells, as well as cultured intrathyriodal T lymphocytes. Proliferation of allogeneic peripheral blood mononuclear cells was stimulated by thyroid follicular cells from both nontoxic goiter and Graves' disease thyroids, thus demonstrating that thyroid follicular cells from both disorders are capable of presenting alloantigens. In contrast the proliferation of autologous peripheral blood mononuclear cells was more efficiently stimulated by thyroid follicular cells from Graves' disease than from nontoxic goiter. Cultured intrathyroidal T lymphocytes proliferated specifically in response to autologous HLA class II+ thyroid follicular cells in Graves' disease, but not in nontoxic goiter. The responses were dose dependent and HLA class II restricted. Thyroid autoantigen presentation by HLA class II expressing thyroid follicular cells thus only occurs in Graves' disease, suggesting that HLA class II expression on thyroid follicular cells is an essential feature, but by itself not sufficient for the induction of autoimmunity. Additional factors, the possible nature of which is discussed must also be involved.